2002
DOI: 10.1016/s0966-6923(01)00033-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of traffic corridor impacts from the introduction of the new Athens Metro system

Abstract: New transit systems are viewed as an effective approach to dealing with concerns about automobile dependence and a degrading quality of life in many large cities. This paper concentrates on evaluating the impacts from the construction of a new subway system as these impacts pertain to traveler behavior and mode choice. Using the results from a revealed preference combined roadside and on-board survey from Athens, Greece, and utilizing a flexible disaggregate model specification (the heteroskedastic extreme val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 6 publications
1
16
0
2
Order By: Relevance
“…However like all other large urban cities, Taipei City also faces serious problems such as traffic congestion, automobile dependence, and automobile emissions, which decrease the quality of living and traveling. In order to solve those problems, many cities invest sizeable amounts in the extension and development of old and the creation of new public transport systems (Golias, 2002). Many researchers argued that rail-based systems can play a critical role in overcoming the problems caused by the automobiles (Ahern, 2001;Newman, 1995;Thornblom & Bengtsson, 1997;Vuchie, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However like all other large urban cities, Taipei City also faces serious problems such as traffic congestion, automobile dependence, and automobile emissions, which decrease the quality of living and traveling. In order to solve those problems, many cities invest sizeable amounts in the extension and development of old and the creation of new public transport systems (Golias, 2002). Many researchers argued that rail-based systems can play a critical role in overcoming the problems caused by the automobiles (Ahern, 2001;Newman, 1995;Thornblom & Bengtsson, 1997;Vuchie, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in Paris, [17] mined spatio-temporal clusters using Paris Velib' data (city bicycle service), but without having access to the user identifier, they could not track individual users. The creation of smart cards to authenticate users [6] allows for wider scale and finer analysis. One important target has been the identification of bottlenecks in the network.…”
Section: Urban Mobilitymentioning
confidence: 99%
“…For example, frequency scales of travels are analyzed in [3] and multiple studies have shown that it is possible to predict most daily travels [19]. For public transports, some early studies focused on opinion pool data to analyze the modification of user behaviors after the creation of new lines [6]. In this domain, quantitative data are recent and linked to the adoption of smart cards to authenticate users in most cities, like e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the factor of price is more important for groups that use public transport than for groups that use individual transport (e.g. Golias, 2002;Nutley, 2003;Spiekermann and Wegener, 1996).…”
Section: Introductionmentioning
confidence: 99%